Bird-flower visitation networks in the Galápagos unveil a widespread interaction release - Traveset, Anna (2015)
Owing to food scarcity and to the high densities that vertebrates often reach on islands, typical insect- and seed-eaters widen their feeding niche and interact with a greater fraction of species than their mainland counterparts. This phenomenon, coined here 'interaction release', has been previously reported for single species but never for an entire community. During 4 years, we gathered data on bird-flower visitation on 12 Galápagos islands. We show that all sampled land birds exploit floral resources and act as potential pollinators across the entire archipelago, in all major habitats and all year round. Although species and link composition varies among islands, strong interaction release takes place on all islands, making their bird-flower network highly generalized. Interaction release is crucial to the survival of native birds but simultaneously threatens the unique biodiversity of this archipelago, as the birds also visit invading plants, likely facilitating their integration into pristine native communities.